(untitled) (International Journal of Engineering and Computer Science, 2014)
Mona, secure data sharing in a multi-owner manner for dynamic groups preserves data, identity privacy from an untrusted cloud and allows frequent change of the membership. In RLS while the number of invoked users grows larger, the length of RL increases. To send all user revocation details to the group members for sharing purpose, leads to communication overhead .To address this issue, in this paper, By leveraging group signature and dynamic broadcast encryption techniques and for overall security Elliptic curve cryptography(ECC) algorithm is used, so that any cloud user can anonymously share data with others. The storage overhead and encryption computation cost of the scheme are independent with the number of revoked users.